The women of Chateau Lafayette - Dray, Stephanie (Berkley, 2021)
"An epic generational saga from New York Times bestselling author Stephanie Dray, based on the true story of an extraordinary castle in the heart of France and the remarkable women bound by its legacy in some of humanity's darkest hours. Most castles are protected by powerful men. This one by women... A reluctant resistor... 1940. French schoolteacher and aspiring artist Marthe Simone has an orphan's self-reliance and wants nothing to do with war. But as the realities of Nazi occupation transform her life in the isolated castle where she came of age, she makes a discovery that calls into question who she is, and more importantly, who she is willing to become. A daring visionary... 1914. Glittering New York socialite Beatrice Astor Chanler is a force of nature, daunted by nothing--not her humble beginnings, her crumbling marriage, or the outbreak of war. But after witnessing the devastation in France and delivering war relief over dangerous seas, Beatrice takes on the challenge of a lifetime: convincing America to fight for what's right. A founding mother... 1774. Gently bred noblewoman Adrienne Lafayette becomes her husband's political partner in the fight for American independence. But when their idealism sparks revolution in France and the guillotine threatens everything she holds dear, Adrienne must choose whether to renounce the complicated man she loves or risk her life for a legacy that will inspire generations to come. Intricately woven and beautifully told, The Women of Chateau Lafayette is a sweeping novel about duty and hope, love and courage, and the strength we find from standing together on the shoulders of those who came before us"--